K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

29 tháng 8 2022

Lại nhá:D

(x+4/3x7/4)=5-7/6

= x + 7/3 = 23/6

= x = 23/6 - 7/3

= x = 3/2 

29 tháng 8 2022

\(x+\dfrac{4}{3}\times\dfrac{7}{4}=5-\dfrac{7}{6}\\ x+\dfrac{7}{3}=\dfrac{23}{6}\\ x=\dfrac{23}{6}-\dfrac{7}{3}\\ x=\dfrac{3}{2}\)

8 tháng 5 2016

a) 47/15

b)77/9

16 tháng 7 2017

  4/3x7 + 5/7x12 + 1/12x13 + 7/13x20 + 3/20x23

=1/3-1/7+1/7-1/12+1/12-1/13+1/13-1/20+1/20-1/23

=1/3-1/23

=20/69

Kanzaki Mizuki

xt19

\(=\frac{1}{3}-\frac{1}{7}+\frac{1}{7}-\frac{1}{12}+\frac{1}{12}-\frac{1}{13}+\frac{1}{13}-\frac{1}{20}+\frac{1}{20}-\frac{1}{23}\)

\(=\frac{1}{3}-\frac{1}{23}\)

\(=\frac{20}{69}\)

26 tháng 3 2017

= 20 / 69 đó 

28 tháng 6 2016

\(\frac{16x17-5}{16x16+11}=\frac{16x16+16-5}{16x16+11}=1\)

\(\frac{4}{3x7}+\frac{5}{7x12}+\frac{1}{12x13}+....+\frac{3}{20x23}\)

=\(\frac{1}{3}-\frac{1}{7}+\frac{1}{7}-\frac{1}{12}+\frac{1}{12}-\frac{1}{13}+...+\frac{1}{20}-\frac{1}{23}\)

=\(\frac{1}{3}-\frac{1}{23}=\frac{20}{69}\)

28 tháng 6 2016

a) \(\frac{16\cdot17-5}{16\cdot16+11}\)

= \(\frac{16\cdot16+16-5}{16\cdot16+11}\)

= \(\frac{16\cdot16+11}{16\cdot16+11}=1\)

16 tháng 8 2017

a)\(A=\frac{2}{3}+\frac{2}{6}+\frac{2}{12}+\frac{2}{24}+\frac{2}{48}+\frac{2}{96}+\frac{2}{192}\)

\(\frac{1}{2}xA=\frac{1}{3}+\frac{1}{6}+\frac{1}{12}+\frac{1}{24}+\frac{1}{48}+\frac{1}{96}+\frac{1}{192}\)

\(\frac{1}{4}xA=\frac{1}{6}+\frac{1}{12}+\frac{1}{24}+\frac{1}{48}+\frac{1}{96}+\frac{1}{192}+\frac{1}{384}\)

\(\frac{1}{4}xA-\frac{1}{2}xA=\frac{1}{3}-\frac{1}{384}\)

\(\frac{1}{4}xA=\frac{127}{384}\)

\(A=\frac{127}{384}:\frac{1}{4}\)

\(A=\frac{127}{96}\)

15 tháng 10 2018

\(\frac{1}{2}+\frac{5}{6}+\frac{11}{12}+\frac{19}{20}+...+\frac{89}{90}\)

\(=1-\frac{1}{2}+1-\frac{1}{6}+1-\frac{1}{12}+1-\frac{1}{20}+...+1-\frac{1}{90}\)

\(=9-\left(\frac{1}{2}+\frac{1}{6}+\frac{1}{12}+\frac{1}{20}+...+\frac{1}{90}\right)\)

\(=9-\left(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+\frac{1}{4.5}+...+\frac{1}{9.10}\right)\)

\(=9-\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+....+\frac{1}{9}-\frac{1}{10}\right)\)

\(=9-\left(1-\frac{1}{10}\right)\)

\(=9-\frac{9}{10}=\frac{81}{10}\)